The Effect of Tri Hita Karana-Based Flipbook Learning on Literacy Skills in Indonesian Language among Grade III Elementary Schools Students - Ni Wayan Sindha Arya Niti; Ni Wayan Rati; Gusti Ayu Putu Sukma Trisna (Mimbar Pendidikan Indonesia, 2025)
This study was motivated by the low literacy levels among elementary school students in Indonesian language learning, as indicated by their lack of reading interest, and the limited availability of engaging and locally relevant learning media. To address this issue, the study aimed to design, test the validity, practicality, and effectiveness of interactive Flipbook teaching materials that integrate Balinese local cultural values through Tri Hita Karana approach to enhance the literacy of third-grade students. The research employed ADDIE model with third-grade students as the subjects. Data were collected through questionnaires and pre- and post-tests. Research instruments included expert validation sheets, practicality forms, and learning outcome test questions. Data were analyzed using descriptive quantitative and qualitative methods, along with inferential statistical analysis. The results showed the developed teaching materials were highly valid, practical, and effective. The Flipbook successfully improved students’ literacy and holds potential as a meaningful and contextual teaching medium.